MORAL VALUES FOUND IN NAOMI SCOTT S SPEECHLESS SONG LYRICS: AN ATTITUDINAL ANALYSIS USING APPRAISAL THEORY (Journal of English Language and Literature Teaching, 2023)
Language is a communication source to deliver information or message In the communication process people use language to express idea opinion thought or desire whether in spoken or written form Following the globalization era music evolves in human daily life Through its lyrics people communicate feelings Message contained in a song is called as moral value This research aimed to describe the moral value of an English song viewed from the perspective of appraisal theory It employed descriptive qualitative approach The object of nbsp; the study is the Aladdin s soundtrack entitled Speechless sung by Naomi Scott released in 2019 The result of the study depicted that the dominant attitude system found is affect system 68 97 followed by appreciation 17 24 and judgement 13 79 The result showed that the songwriters mostly using their feelings in its lyrics The feeling that dominantly appeared are positive feelings of fearlessness confidence and bravery Furthermore the prominent attitude of the song is inscribed attitude 72 72 that indicated directly conveyed and followed by invoked attitude 27 27 Related to feminism the song delivered message in which women should not be underestimated and all the old stigmas which weaken women position should be against in order to achieve equality among genders Based on the analysis the song can contribute in material development for the sound argument teaching < p>
Keywords: Appraisal Theory; Feminism; Moral Value